Parental needs and stress in Neonatal Intensive Care Units: effect of data collection period - Baía, I (2015)
The assessment of parental needs and stress is essential for the implementation of quality family-centred care in Neonatal Intensive Care Units (NICUs). Therefore, we aim to assess the effect of data collection period on self-reported needs and stress among parents of very preterm infants hospitalized in level III NICU, comparing those interviewed 8-14 days after child s admission with those interviewed 15-22 days after that event. Between January and September 2013, parents filled the NICU Family Needs Inventory and the Parental Stress Scale in NICU. Needs of assurance and proximity were the most valued, independently of the time of interview. A tendency for attributing a higher relevance to support needs and to stress levels regarding change in parental role was observed throughout the hospitalization.